PPLK STUDENT’S COMPETENCE OF EDUCATION BUILDING TECHNIQUES PROGRAM PADANG STATE UNIVERSITY BASED ON TEACHER’S GUIDE ASSESSMENT OF SMK IN WEST SUMATERA - 818-826 , Tri Mardi Jaya Putra (Universitas Negeri Padang, 2015)
Abstract This research is descriptive research which intends to explore the competence of PPLK student’s Education Building Techniques program based on the assessment of guide teachers of SMK in West Sumatera of semester July-August 2014 seen from the student’s pedagogic competence, personality, social and professional. The population of this research is the whole guide teachers of SMK in West Sumatera which guide the PPLK student of Education Building Techniques programFaculty of engineering Padang State University semester July-Desember 2014. The technique of taking the sample used in this research is total sampling as many as61 people. The data was collected by using questionnaire with skala likert consisting of 4 answering options. The amount of statement in research questionnaireis as many as 50 particles of statement. Based on the result of the research, it is earned that the student PPLK’s pedagogic competence achievement major is 69,24% with enough category. The PPKL student’s personality competence is 66,42% with enough category. The student PPLK’s social competence is 63,36% with less category. The PPLK student’s professional competence is 69,58% with enough category. Key words : Kompetensi, Mahasiswa PPLK, Penilaian Guru Pamong.